PERANCANGAN PURWARUPA STIKER FACEBOOK SEBAGAI SARANA MENG-COUNTER POSTINGAN HOAX - Eko Saputro, Godham; Haryadi, Toto (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
Hoax or fake news is a case which disturbs society because it was shared by irresponsible people. One of social media which is often used for sharing hoax is facebook in order to persuade people’s opinion and also create their own perception. The purpose of this research is create prototype of facebook stickers as medium to againts hoax. Facebook stickers is chosen because it has more value and according to the audiences. The method which is used for reasearch is qualitative descriptive, that is describes problem about hoax and its complexity in the social scope. Data in this research were obtain through observation and study of literature. The result of analysis is a design concept of facebook stickers that will be designed by researchers in form of prototype, where is new innovation will againts news which is not valid.